Teaching Business English with TED Talks: Putting Ideas into Practice - Olga Stognieva (National Research University Higher School of Economics, 2019)
TED.com is used in teaching EFL to enhance exposure to English, to promote authentic vocabulary and to develop multiple foreign language skills. For university students studying business as their major and English for professional communication as a part of their university curriculum, TED talks provide a cutting-edge business context, which aims to increase the learners' English language proficiency, develop the learners' professional competencies and expand their outlook by acquainting them with business practices from around the world. Through authentic models of effective communication, students build fluency to achieve academic and personal success. Business English with TED talks, an EFL resource book, is the result of the author's approach to creating educational materials based on authentic and up to date video content. Using the example of 'Business English with TED talks', this paper describes criteria for selecting TED talks for different groups of students, the structure of a TED talk lesson and provides teachers with other resources for supplementing TED talk lessons.